The Effect Of The Problem Based Learning (PBL) Learning Model And Quizizz Learning Media On The Learning Interest Of Grade IV Students At Gmim IV Tomohon Elementary School - Falda Freiti Kapahang; Deitje A. Katuuk; Deysti T. Tarusu (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to determine the effect of the use of the Problem Based Learning (PBL) learning model and Quizizz learning media on the learning interest of fourth-grade students at GMIM IV Elementary School, Tomohon. This study used a quantitative approach with a one-group pretest-posttest experimental design. The research subjects were 30 fourth-grade students. Data collection techniques in this study included observation, questionnaires with a Likert scale, and documentation. The research instrument was a learning interest questionnaire that measured indicators of feelings of pleasure, interest, attention, active participation, and learning motivation. Data were analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results showed that there was an increase in student learning interest after the implementation of PBL and Quizizz. The average pretest score in the experimental class was 62.5, increasing to 85.3 in the posttest, with a difference in increase of 22.8, while the control class only increased by 7.1. The partial test results (t) show that the PBL model has a significant effect on students' learning interest (Sig. 0.000 < 0.05), and the Quizizz media also has a significant effect (Sig. 0.002 < 0.05). Simultaneously, both variables have a significant effect on students' learning interest (Sig. 0.001 < 0.05). Thus, it can be concluded that the use of the PBL learning model combined with the Quizizz media is effective in increasing students' learning interest. Keywords: Problem Based Learning, Quizizz, interest in learning